Gambaran Tingkat Kepuasan terhadap Pelayanan Pasien yang Menjalani Operasi Sectio Caesarea Dengan Menggunakan Metode ERACS - Waraiya, Heni Safitri; Novitasari, Dwi; Setyawati, Martyarini Budi (Pusat Riset dan Inovasi Nasional, 2026)
Cesarean section is one of the most frequently performed surgical procedures, with an incidence that continues to increase every year. The risk of complications and longer hospitalization remains a challenge in its management. One effort to improve service quality and patient satisfaction is the implementation of the Enhanced Recovery After Surgery (ERACS) method. This study aims to describe the level of patient satisfaction with services using the ERACS method in patients undergoing cesarean section. This research is a descriptive quantitative study with a cross-sectional approach. The sample consisted of 70 patients who underwent cesarean section with the ERACS method at Dr. Soedirman General Hospital Kebumen, selected using purposive sampling. The research instrument was a questionnaire based on five satisfaction dimensions of SERVQUAL. The results showed that most respondents were satisfied (57.1%) and very satisfied (40%). The conclusion of this study is that the ERACS method contributes positively to increasing patient satisfaction, particularly in terms of comfort, recovery speed, and service information provided.